Peirce's Twenty-Eight Classes of Signs and the Philosophy of Representation Rhetoric, Interpretation and Hexadic Semiosis - Jappy, Tony (Bloomsbury Advances in Semiotics, 2016)
The major principles and systems of C. S. Peirce's ground-breaking theory of signs and signification are now generally well known. Less well known, however, is the fact that Peirce initially conceived these systems within a 'Philosophy of Representation', his latter-day version of the traditional grammar, logic and rhetoric trivium. In this book, Tony Jappy traces the evolution of Peirce's Philosophy of Representation project and examines the sign systems which came to supersede it. Exploring the potential of the later sign-systems that Peirce scholars have hitherto been reluctant to engage with and extending Peirce's semiotic theory beyond the much canvassed systems of his Philosophy of Representation, this book will be essential reading for everyone working in the field of semiotics.